2002
DOI: 10.1590/s0100-879x2002000200013
|View full text |Cite
|
Sign up to set email alerts
|

Acute buspirone abolishes the expression of behavioral dopaminergic supersensitivity in mice

Abstract: Previous studies have shown that rats withdrawn from long-term treatment with dopamine receptor blockers exhibit dopaminergic supersensitivity, which can be behaviorally evaluated by enhanced general activity observed in an open-field. Recently, it has been reported that co-treatment with the non-benzodiazepine anxiolytic buspirone attenuates the development of haloperidol-induced dopaminergic supersensitivity measured by open-field behavior of rats. The aims of the present study were: 1) to determine, as prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…We recently found that systemic administration of the 5-HT 1A R agonist ±8-OH-DPAT reduced D1R agonist-induced dyskinesia while enhancing rotations, implicating an important functional role between 5-HT 1A R and D1R (Dupre et al, 2007). In line with these effects, 5-HT 1A R stimulation has been shown to reduce overactive striatal D1R-mediated signaling and D1R-mediated behaviors associated with the expression of LID (Queiroz et al, 2002; Tomiyama et al, 2005). …”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…We recently found that systemic administration of the 5-HT 1A R agonist ±8-OH-DPAT reduced D1R agonist-induced dyskinesia while enhancing rotations, implicating an important functional role between 5-HT 1A R and D1R (Dupre et al, 2007). In line with these effects, 5-HT 1A R stimulation has been shown to reduce overactive striatal D1R-mediated signaling and D1R-mediated behaviors associated with the expression of LID (Queiroz et al, 2002; Tomiyama et al, 2005). …”
Section: Discussionmentioning
confidence: 74%
“…Although both receptor subtypes appear to be involved in LID, striatal D1R are particularly important (Cenci et al, 1998; Gerfen et al, 2002; Guigoni et al, 2007; Westin et al, 2007). For example, striatal preprodynorphin (PPD) mRNA associated with the D1R-expressing direct pathway (Anderson & Reiner, 1990) is increased in dyskinetic rats and primates and reduced by a number of anti-LID treatments (Cenci et al, 1998; Queiroz et al, 2002; Mela et al, 2007). Furthermore, coadministration of a D1R antagonist with L-DOPA has recently been shown to completely block the development of L-DOPA-induced dyskinesia and associated molecular abnormalities in a rodent model of LID (Westin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The function of 5-HT 1A receptor in individual animals can be evaluated by differences in behavior after administration of a 5-HT 1A receptor agonist. Such responses include anxiolytic-like behavior in the open field and/or elevated plus maze [ 22 , 32 , 33 ], 5-HT syndrome (flat body posture, Straub tail response, hind limb abduction, forepaw treading, and head weaving behavior) [ 34 37 ], and hypothermic responses [ 38 , 39 ]. A dose-dependent decrease in rearing was observed following administration of buspirone, a 5-HT 1A receptor partial agonist, in the open field or elevated plus maze [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, direct intrastriatal infusions of NMDAR antagonists produce both antiparkinsonian and anti-dyskinetic effects (Marin et al 1996;Nash et al 1999;Nash and Brotchie 2000). Similarly, stimulation of 5-HT 1A R within the motor cortex and/or striatum may convey anti-parkinsonian or anti-dyskinetic effects in part through a reduction of glutamate levels at the NMDAR (Antonelli et al 2005;Wolf 2005, 2007) via coincident effects on D1R-mediated signaling (Queiroz et al 2002;Tomiyama et al 2005;Ba et al 2006;Campbell et al 2006). Clearly, further work is necessary to investigate these novel results.…”
Section: Discussionmentioning
confidence: 99%